Practices of reconciliation in the Anlong Veng Community, Cambodia - Sovann Mam (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This thesis examines the processes of reconciliation that have taken place in post-genocide Cambodia. In doing so, the thesis follows a case study of Anlong Veng, the last stronghold of the Khmer Rouge (KR), to examine how and to what extent the strategy of the Cambodian government of the 1990s has achieved reconciliation, and how reconciliation process between victims and former Khmer Rouge cadres can be further advanced. While the country is not currently at war and the Extraordinary Chambers in the Courts of Cambodia (ECCC) has prosecuted senior leaders and those most responsible for crimes committed during the Khmer Rouge years, thousands of former Khmer Rouge cadres live among the general population in the midst of victims of the regime. This thesis examines the contributions of the ECCC and of Cambodian non-governmental organizations (NGOs) to the reconciliation process. It also analyzes local perceptions of reconciliation. It argues that although the government and stakeholders have achieved important progress, reconciliation efforts at personal and community levels remain incomplete. This thesis shows that even as the KR Tribunal is delivering retributive justice, many victims still want to hear the acknowledgments and confessions of those who committed crimes during the Khmer Rouge regime. The analysis is based on a literature review and qualitative research interviews conducted in 2016 and 2019.